Lymph node number, surface area and lymph node ratio are important prognostic indicators in neoadjuvant chemoradiotherapy treated rectal cancer. Issue 3 (25th September 2019) - Pitto, Francesca; Zoppoli, Gabriele; Scabini, Stefano; Romairone, Emanuele; Fiocca, Roberto; Ballestrero, Alberto; Sparavigna, Marco; Malaspina, Lara; Valle, Luca; Grillo, Federica; Mastracci, Luca
Abstract : Aims: Neoadjuvant chemoradiotherapy (neoCRT) is recommended for locally advanced rectal cancer (RC), however, this often makes lymph node (LN) search trying. The aim of this study was to evaluate, in a large retrospective, monocentric, series of post-neoCRT-RC patients, the importance of LN number, ratio and surface area in predicting metastases, overall survival (OS) and disease free survival (DFS). Methods: 104 patients with RC underwent total mesorectal excision, after standard neoCRT. All resected specimens were examined according to a standardised sampling/histopathological protocol. The following data regarding LNs were collected: total numbers; number with metastases; LNratio (metastatic/total); maximum diameter; surface area. Results: A statistically significant association was found between LN number and DFS (p=0.0473). Finding ≤9 or >20 LNs correlated with worse prognosis compared with 10–20 (p value=0.049). LNratio (>0.2) was strongly associated with shorter DFS (HR=13.36; p value <0.0001) and OS (HR=26.06; p value <0.0001). Poor outcome, for DFS (HR=2.17, p value =0.0416) and OS (HR=1.18, p value =0.0025), was associated with increasing LN surface area. LNratio was independently associated with DFS at multivariate analysis (p value <0.0001). Conclusions: LN number, LNratio and LN surface area are important prognostic factors in neoCRT-RC and in particular finding ≤9 or >20 LNs is prognostically adverse.